Driverless Car: Autonomous Driving Using Deep Reinforcement Learning in Urban Environment - Fayjie, Abdur R.; Hossain, Sabir; Oualid, Doukhi; Lee, Deok-Jin (2018 15th International Conference on Ubiquitous Robots (UR), 2018)
Deep Reinforcement Learning has led us to newer possibilities in solving complex control and navigation related tasks. The paper presents Deep Reinforcement Learning autonomous navigation and obstacle avoidance of self-driving cars, applied with Deep Q Network to a simulated car an urban environment. The approach uses two types of sensor data as input: camera sensor and laser sensor in front of the car. It also designs a cost-efficient high-speed car prototype capable of running the same algorithm in real-time. The design uses a camera and a Hokuyo Lidar sensor in the car front. It uses embedded GPU (Nvidia-TX2) for running deep-learning algorithms based on sensor inputs.